Effect of Branding and Familiarity of Soy Sauces on Valence and Arousal as Determined by Facial Expressions, Physiological Measures, Emojis, and Ratings - de Wijk, Rene A.; Ushiama, Shota; Ummels, Meeke J.; Zimmerman, Patrick H.; Kaneko, Daisuke; Vingerhoeds, Monique H. (Frontiers in Neuroergonomics, 2021)
Food experiences can be summarized along two main dimensions: valence and arousal, which can be measured explicitly with subjective ratings or implicitly with physiological and behavioral measures. Food experiences are not only driven by the food's intrinsic properties, such as its taste, texture, and aroma, but also by extrinsic properties such as brand information and the consumers' previous experiences with the foods. In this study, valence and arousal to intrinsic and extrinsic properties of soy sauce were measured in consumers that varied in their previous experience with soy sauce, using a combination of explicit (scores and emojis), implicit (heart rate and skin conductance), and behavioral measures (facial expressions). Forty participants, high- and low-frequency users, were presented with samples of rice and three commercial soy sauces without and with brand information that either matched or non-matched the taste of the soy sauce. In general, skin conductance and facial expressions showed relatively low arousal during exposure to the brand name and again lowest arousal during tasting. Heart rate was lowest during exposure to the brand name and increased during tasting probably resulting from the motor activity during chewing. Furthermore, the results showed that explicit liking and arousal scores were primarily affected by the taste of the specific soy sauce and by the participants' previous experience with soy sauces. These scores were not affected by branding information. In contrast, facial expressions, skin conductance, and heart rate were primarily affected by (1) the participants' level of experience with soy sauce, (2) whether or not branding information was provided, and (3) whether or not the branding information matched with the taste. In conclusion, this study suggests that liking scores may be most sensitive to the food's intrinsic taste properties, whereas implicit measures and facial expressions may be most sensitive to extrinsic properties such as brand information. All measures were affected by the consumers' previous food experiences.